2017
DOI: 10.1007/s10815-017-0996-1
|View full text |Cite
|
Sign up to set email alerts
|

Low first-trimester PAPP-A in IVF (fresh and frozen-thawed) pregnancies, likely due to a biological cause

Abstract: Consistent with previous studies IVF pregnancies had significantly lower PAPP-A levels supporting the need to appropriately adjust the combined first-trimester screening (cFTS) risk algorithm for IVF conceptions. The Brahms Kryptor and Immulite 2000 platforms are significantly different; however, the universally lower PAPP-A findings support the hypothesis that the lower PAPP-A is due to a biological cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
8
1
1
Order By: Relevance
“…It has been suggested that hormonal treatment is the most important cause of altered biochemical markers in IVF pregnancies. The supra-physiologic oestrogen level and premature progesterone secretion due to ovarian stimulation may result in a non-synchronous uterine environment, a suboptimal placenta-endometrial interface and impaired placentation [6,8,11,31]. This hypothesis was supported by findings that first-trimester maternal serum PAPP-A levels are affected by the oestradiol level at the time of oocyte retrieval and by the number of oocytes in IVF cycles [27,32].…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that hormonal treatment is the most important cause of altered biochemical markers in IVF pregnancies. The supra-physiologic oestrogen level and premature progesterone secretion due to ovarian stimulation may result in a non-synchronous uterine environment, a suboptimal placenta-endometrial interface and impaired placentation [6,8,11,31]. This hypothesis was supported by findings that first-trimester maternal serum PAPP-A levels are affected by the oestradiol level at the time of oocyte retrieval and by the number of oocytes in IVF cycles [27,32].…”
Section: Discussionmentioning
confidence: 93%
“…Women who become pregnant after undergoing ovarian stimulation, which results in high levels of estradiol, show significantly lower levels of PAPP-A as compared to women who become pregnant naturally [32,33]. This has been measured at the end of the first trimester in connection with prenatal screening, and the reference interval for normal PAPP-A levels is reduced if the woman underwent ovarian stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the cause of infertility, it is possible to become pregnant for infertile women by using assisted reproduction technology. Various studies have shown that children born through infertility treatments, particularly IVF, have more congenital anomalies than normal births (7)(8)(9)(10)(11)(12). Prevention of chromosomal abnormalities is only possible via doing the screening tests, detecting malformations, and terming this pregnancy with family consent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children who are born via fertility treatment, particularly IVF, have more congenital anomalies than the babies from normal-conception (3-7). Hunt et al (8) showed that PAPP-A levels in those who have been treated by assisted fertility methods, such as IVF, were higher than those who became pregnant spontaneously. It could be a result of the ICSI technique through microinjection that makes bleeding in zona pellucida so that the placenta and biochemical tests in the first trimester can be affected (8).…”
Section: ) Genetic Council After Examinations To Interpret and Justimentioning
confidence: 99%
See 1 more Smart Citation